Media For Effective Instruction of Islamic Education - Sumiyati; Muafaq, M. Fadil; Susilowati, Samsul (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
Education is a basic foundation for world progress. With education, humans can differentiate between all things, whether positive or negative. One of the success factors is the use of media, namely by making media an effective instruction in the learning process in the world of education. The purpose of this article is to find out how to integrate media as effective instruction in the learning process and what types of media as effective instruction are used in the learning process. The type of research in this article is literature based, namely using literature as a collection of data sources using a qualitative research approach. Media as a teaching tool that helps educators to spread knowledge in an impressive way so as to provide diversity in classroom teaching and make learning more effective and interesting. Media becomes an effective form of instruction if educators are able to master its use and utilization so that students' interest and understanding in learning increases and the success of the learning process has a great chance of achieving the educational goals being implemented.